183k views
4 votes
2x + y = 4y = 3x - 1 is (1, 2) a solution to both equations?

User Rulle
by
5.0k points

1 Answer

3 votes

The given system of equations is expressed as

2x + y = 4

y = 3x - 1

We would apply the method of substitution by substituting equation 2 into equation 1. It becomes

2x + 3x - 1 = 4

5x - 1 = 4

5x = 4 + 1

5x = 5

x = 5/5

x = 1

Substituting x = 1 into the second equation, it becomes

y = 3 * 1 - 1

y = 3 - 1

y = 2

Therefore, (1, 2) is a solution to both equations

User Phanin
by
5.3k points